Blood pressure and salt intake in Malawi: an urban rural study. Issue 2 (June 1986) - Simmons, D; Barbour, G; Congleton, J; Levy, J; Meacher, P; Saul, H; Sowerby, T
Abstract : A significant difference between the blood pressures of rural and urban Malawians was found in both sexes, was present at the age of 15 years, and was associated with obesity but not with smoking, alcohol consumption, occupation or housing. Pulse rate was significantly lower in the urban group. These differences were accompanied by low potassium and sodium intake although the sodium intake in the urban group was double that in the rural group. No direct relation between blood pressure and urinary electrolytes was found.